Learning to Kill by Proxy: Colombian Paramilitaries and the Legacy of Central American Death Squads, Contras, and Civil Patrols - Sanford, Victoria (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. An examination of the origins of Colombian paramilitaries in the cold war era, when the U.S. helped the Colombian and Central American governments set up proxy paramilitary forces in its battle against “international Communism” is presented. The horrific consequences that this paramilitarism had for Colombian and Central American society during the 1960s to the late 20th century are considered. An update on the impact of paramilitarism on human rights in contemporary Colombia, and on the ramifications for peace in the region, is provided.